Effect of Vitamin D on proteinuria, lipid status, glycoregulation and C-reactive protein in patients with type-2 diabetes mellitus - Petrović, Marijana; Dragović, Tamara; Petrović, Stanko; Obrenčević, Katarina; Rančić, Nemanja; Djurašinović, Tatjana; Petrović, Dejan; Ignjatović, Ljiljana; Rabrenović, Violeta; Nenezić, Nemanja; Marinković, Dejan; Maksić, Djoko (Vojnosanitetski pregled, 2021)
Background/Aim. Vitamin D insufficiency/deficiency is often present in patients with type-2 diabetes mellitus (DM) and could present a risk factor for rapid progression of diabetic nephropathy and for higher incidence of cardiovascular events. The aim of this study was to examine the influence of vitamin D supplementation on proteinuria, cholesterol, triglycerides, C-reactive protein (CRP) and hemoglobin A1c in patients with type-2 DM and vitamin D insufficiency/deficiency. Methods. This prospective, cohort study included 90 patients with type-2 DM and vitamin D insufficiency/deficiency divided into 3 equal groups: with normal proteinura, with microproteinuria and with macroproteinuria. Therapy included six months of supplementation with cholecalciferol drops: first two months with 20,000 IU twice weekly, than if level of vitamin D was below normal the same dose was given next four months. If the level of vitamin D was normal 5,000 IU was given twice weekly. At the begining and at the end of the study the levels of urea, creatinine, fasting blood glucose, calcium, phosphorus, cholesterol, triglycerides, CRP, hemoglobin A1c, intact parathyroid hormone, 24-hour urine protein and creatinine clearance were determined. Levels of calcium, phosphorus and vitamin D were also checked 2 months after beginning of therapy due to possible correction of cholecalciferol dose. Results. The lowest level of vitamin D before therapy was found in patients with macroproteinuria, while at the end of the study the significantly higher level of vitamin D was found in all three groups. After 6 months of therapy a significant decrease of 24-hour urine protein, cholesterol, triglycerides, hemoglobin A1c in all three groups, and CRP in patients with normal proteinuria and microproteinuria were found. Significantly negative correlation between vitamin D and 24-hour urine protein, cholesterol and CRP was found in patients with macroproteinuria. Also, significantly negative correlation was found between vitamin D and hemoglobin A1c, in patients with normal proteinuria, vitamin D and CRP in patients with microproteinuria. Conclusion. A preventive use of high-dose cholecalciferol supplementation in patients with type-2 DM (with or without proteinuria) decreases cholesterol, triglycerides, proteinuria, CRP and hemoglobin A1c.